The Effect of Tourism Accessibility Perception Towards Tourists Visiting Intention to Toba Lake in Samosir District - Napitupulu, Dina Wati Veronika; Rahmafitria, Fitri; Rosita, Rosita (Journal of Indonesian Tourism, Hospitality and Recreation, 2021)
ABSTRACTThis study aims to see the effect of perceptions received by tourists visiting intention to Toba Lake, Samosir Regency. A quantitative approach method was used by using statistical data in multiple regression analysis. The population was domestic tourists and the sample was 325 respondents who were obtained using random sampling techniques. The results were divided into (1) a significant effect and positive destination accessibility and simultaneously on the intention in tourist visits 2) the ability of the independent variables in explaining the related variables was 53.8% the remaining 46.2% from other variables not discussed in this study 3) the influence of accessibility variable on tourists' visiting intention is strong. From these results it can be concluded that accessibility according to the Apollo concept needs to be improved by the manager of tourist destinations at Toba Lake because the role of accessibility affects the intention to visit tourists to Toba Lake. Keywords: Real Accessibility, Destination Accessibility, and Visiting Intention